Pregnancy and Childbirth: Postpartum Anxiety (PPA) and Support for New Mothers - Sawers, Melissa; Wong, Gina (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
Perinatal mood and anxiety disorders (PMADs) are a significant mental health concern worldwide. In Canada, researchers, maternal mental health advocates, and practitioners are working to increase understanding of mental health in the perinatal period. This article focuses on the necessity to expand and build upon current understanding of PMADs, particularly postpartum anxiety disorders (PPA). The traditional construct of postpartum depression (PPD) is inadequate to understand, assess, diagnose, and treat the wide range of postpartum mood disorders. Anxiety disorders may be underdiagnosed among new mothers. Specific risk factors are explored for this population and support interventions are provided for PPA. Additionally, this article explores ways to improve understanding of PMADs from a sociocultural perspective and to improve protective factors that may enhance a new mother’s mental health. Addressing the gaps and needs in postpartum mental health will positively affect mothers, fathers, their families, and our communities.